AN ANALYSIS OF THE BIOLOGICAL TERMS TRANSLATION IN THE BOOK ENTITLED "BIOLOGY 1: BILINGUAL STUDENT TEXT BOOK FOR SENIOR HIGH SCHOOL, YEAR X"(A case study of English-Indonesian Translation of Biological Terms) - Tian Setiawati Topandi, - (2010)
This study is entitled An Analysis of the Biological Terms Translation in the Book Entitled "Biology 1: Bilingual Student Text Book for Senior High School, Year X". The study presents the analysis of the translation procedures used in translating biological terms of the book as proposed by Catford (1965), Vinay and Darlbenet (1958), Larson (1984), Newmark (1988), and Delisle (1999). In addition, the researcher also provides the quality of translation according to Larson (1984), accuracy, clarity, and naturalness. The researcher found out that the transference was the most frequent procedure used by the translator in translating biological terms in the book. However, there were also the other kinds of translation procedure used in the book: naturalization, literal, couplets, triplet, through, and synonymy. In addition, based on the questionnaire given to the three biology teachers, the quality of biological terms translation was in "Good" level. Hopefully this study could give fresh ideas for further studies.